THE REALIZATION OF MORPHOSYNTAX, PRAGMATICS, PHONOLOGY, AND LEXICON IN VIVIAN’S CONTEXT OF ENGLISH LANGUAGE TEACHING - Imam Munandar (Asosiasi Dosen Perguruan Tinggi Islam, 2019)
This research has found that he language and language learning theories in Vivian’s classroom follow the communicative and cognitive/ interactionism approach. Vocabulary, pronunciation, morpho-syntax and pragmatics were learnt interactively in the classroom. Cognitive theory crucially considers learning language as a process, and interactionism views language as acquired when learners are involved in interaction. These approaches are finely exemplified in the classroom activities. Interactionist centralizes the role of input, interaction and output. Input and interaction are modified to make it comprehensible for the students. Noticing is central to input to be uptake. In Vivian’s classroom, opportunity for output is provided for the students to exercise their emergent language. Furthermore, feedback is given to indicate learners’ incorrect forms of the language, leading them to notice the form of language they need to work on. Knowing a word involves the identification of form, meaning, and use. In lexicon learning, it is important for teachers to the build semantic fields of the words. Attaining this, as Vivian showed, it is helpful to provide input with visual aids to enhance learners’ conceptualization of a particular word.